Partners we can trust: the role of employee engagement influencing partnerships’ relationship quality in the voluntary sector - Marques, S.; Bilro, R. G.; Gonçalves, M.; Raouf, A. R. (Management Research: The Journal of the Iberoamerican Academy of Management, 2022)
Purpose – This paper aims to explore if employee engagement (EE) influences the relationship quality of long-term partnerships between non-profit organisations (NPO) and for-profit organisations (FPO) and offer a theoretical framework for NPO and FPO long-term partnerships’ success based on the literature. Design/methodology/approach – The study resorts to qualitative research, and through 45 in-depth structured interviews with NPO and FPO employees, this paper intends to investigate the theoretical framework using a hypothetico-deductive method. Findings – The findings support the authors’ theoretical framework, where EE influences satisfaction, trust and commitment to the partnership. The results highlight that organisations creating high levels of satisfaction, trust and commitment may have a higher propensity for long-term partnerships. Originality/value – This study offers a novel theoretical framework for developing long-term partnerships between NPO and FPO. However, each variable’s extent of influence still needs to be further explored, creating a fertile ground for future research in this area.